Permanent Resident - Ongkowidjaja, Nadia Priscilla (2016)
In this project titled “Permanent Resident”, I would be focusing on my perplexed life as a Permanent Resident in Singapore. I consider my life to be perplexed as my roots had been unknown to me for the past twenty-two years and am consequently still unsure of who I am. My citizenship and place of residence were decided by the previous generation and hence I have never lived in nor known my native country. I therefore reside in a land that I consider home and yet do not fully belong. Thus, my understanding of who I am is minimal, and standing in society, fairly questionable. I intend to research on my heritage, where my ancestors originated from, the intent of their migration and how I came to be in Singapore. As one who has always felt at a loss of who she is, I would also be addressing this confusion as a Permanent Resident in Singapore. I have struggled internally as a Permanent Resident in Singapore and had to come to terms with the conditions of being one. This study therefore gives me the opportunity to figure out who I am and my place in society.